Interação de ectoparasitos e pequenos mamíferos não voadores em área fragmentada na Amazônia meridional - Mendonça, Ravena Fernanda Braga de (2018)
Ectoparasites are influenced by inherent factors to the host such your identity, body size, physiology and environment outside the host. Small non-flying mammals are considered a diverse group of species and harbours ectoparasites responsible for transmission of pathogens for diverse organisms. The Amazonia rainforest has a few researches in the field. The aim this research is analyze the influence of body size host and environment structure outside the host such the litter, understorie forest and canopy openness in the ectoparasites structure (richness and abundance) associated with small mammals, and verify if ectoparasites assembly shows a nested pattern in a fragmented region. The research area is inserted in a transition region between Amazonian rainforest and Cerrado, located in the municipality of Sinop, state of Mato Grosso. Small mammals were collected between november and december of 2016 in 17 transect lines of 300 meters in length each. We meansured host body size and colected their ectoparasites. In addition, environmental measures such as volume of litter, percent of understories and canopy openness also were withdrawn in each sampling site. GLM analysis were made for richness and abundance of ectoparasites associated with small mammals. Null model of index NODF was made in each site to assess if the ectoparasite assembly has a nested pattern or overdispersed in the hosts. A total of 58 small mammal were collected, belonging to four marsupials and five rodents species were sampled; 39 individuals were parasited by 14 ectoparasites taxons totalling n=627 (five Metastigmata, four Siphonaptera, two Mesostigmata, one Prostigmata and one Phthiraptera). The host body size affected richness and abundance of fleas and ticks. For mites of the order Mesostigmata just the abundance was affected. Environmental variables affected the richness of the fleas and abundance of the three orders cited earlier. The nested has been significative just for one site which represented an great richness of ectoparasites (n=11) sheltered in just four individuals. The results demonstrate as some ectoparasites are more representative than other in comparison to some researches of different regions of the country, have also been influenced by hosts samples and their natural habitat.